Pengaruh Pembelajaran Agama Islam dan Budi Pekerti Berbasis Multikultural dan Sikap Sosial Terhadap Sikap Toleransi Keberagamaan Siswa Kelas X SMA Negeri 4 Kota Bengkulu - Linda Linda; Mus Mulyadi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
The type of research used in this study is quantitative research, the research instrument used is a questionnaire, the data analysis technique used is descriptive statistics, basic assumption test, classical assumption test, and hypothesis test using simple linear regression and multiple linear regression, t test and F test. Research results (1) There is an influence of Islamic religious learning and multicultural-based morals on the attitude of religious tolerance of class X students at SMA Negeri 4 Kota Bengkulu which is shown in the calculated t (2,053) > t table (5% = 1.70) and a significance level of 0.046 < 0.05. So in this test it shows that Ha is accepted. (2) There is an influence of social attitudes on the attitude of religious tolerance of class X students at SMA Negeri 4 Bengkulu City which is shown in the t count (2.862) > t table (5% = 1.70) and a significance level of 0.007 < 0.05. So in this test it shows that Ha is accepted. (3) There is an influence of Islamic religious learning and character based on multiculturalism and social attitudes on the attitude of religious tolerance of class X students at SMA Negeri 4 Bengkulu City which is shown in the t count (3.875) > t table (5% = 2.85) and a significance level of 0.032 < 0.05. So in this test it shows that Ha is accepted.